1999
DOI: 10.1095/biolreprod61.6.1541
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Is Physiologically Restricted to a Specialized Cytoplasmic Compartment in Rat Spermatids

Abstract: Cytoplasmic caudal tags of maturing spermatids condense and are detached from the spermatidal cells just before the spermatids are released as spermatozoa. The detached cytoplasmic masses are termed "residual bodies." Features of residual bodies seem to be compatible with those of apoptosis and, just as occurs with apoptotic bodies, residual bodies are phagocytosed by Sertoli cells. Since in vitro studies have demonstrated that nucleus and cytoplasm apoptosis events can be independent phenomena, we reasoned th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
1
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 53 publications
2
63
1
6
Order By: Relevance
“…These intercytoplasmic bridges are eliminated after completion of meiosis during spermiogenesis. In mammals, caspase-1-like activity was suspected in spermatids, 40 but our results show that caspase-3 is also involved in terminal maturation of haploid cells and /or syncitia removal, and caspase-9 earlier in maturation of the spermatid heads. This agrees with the caspase-3 labeling of mature spermatozoa.…”
Section: Discussionmentioning
confidence: 50%
“…These intercytoplasmic bridges are eliminated after completion of meiosis during spermiogenesis. In mammals, caspase-1-like activity was suspected in spermatids, 40 but our results show that caspase-3 is also involved in terminal maturation of haploid cells and /or syncitia removal, and caspase-9 earlier in maturation of the spermatid heads. This agrees with the caspase-3 labeling of mature spermatozoa.…”
Section: Discussionmentioning
confidence: 50%
“…Interestingly it has been recently reported that apoptosis-like mechanisms are required for spermatid differentiation in Drosophila (Arama et al, 2003). An analogy between cytoplasmic apoptotic events and the formation of residual bodies has been also noticed in mammalian spermiogenesis (Blanco-Rodriguez and Martinez-Garcia, 1999). On the other hand, Bax was reported to be expressed, besides in spermatogonia and Sertoli cells, also in spermatocytes (Yan et al, 2000), but we found an abundant transcript in mitotic germ cells and in Sertoli cells, with the highest level of expression at 7 dpn, whereas only a very faint signal was detectable in spermatocytes (Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Residual bodies exhibit similar protein contents and morphology, as do apoptotic bodies (Blanco-Rodriguez and Martinez-Garcia, 1999). They are pinched o by the elongated spermatids before they leave the seminiferous tubules and are then, like apoptotic bodies in the testis, phagocytized by Sertoli cells.…”
Section: Discussionmentioning
confidence: 94%